EXPLORATION OF PROBLEM-POSING ABILITY OF THE STUDENTS OF CLASS VII-D OF STATE JUNIOR HIGH SCHOOL 4 KINTAMANI THROUGH MATHEMATICAL PROBLEM-BASED ETHNOMATHEMATICS - Darmayasa, Jero Budi (MATEMATIKA DAN PEMBELAJARAN, 2019)
Penelitian ini merupakan penelitian deskriptif. Penelitian bertujuan untuk mengeksplorasi dan mendeskripsikan kemampuan Problem Posing siswa kelas VII SMPN 4 Kintamani terutama pada dimensi kreatif. Berdasarkan data yang diperoleh, diketahui bahwa siswa Kelas VII secara umum sudah mulai menunjukkan kreativitasnya dalam mengajukkan soal/pertanyaan berkaitan dengan matematika. Disamping itu, pemberian soal-soal matematika berbasis Ethnomathematics atau Mathematical Problem based Ethnomathematics (MPbE) memberikan warna tersendiri dalam diskusi kelas, karena bagi siswa merupakan hal baru. Mereka baru menyadari bahwa berbagai aktivitas agama dan budaya yang selama ini dilakukan berkaitan dan bahkan kaya dengan konsep-konsep matematika seperti yang mereka pelajari di sekolah. Kata kunci: Ethnomathematics, PBL, Problem Posing This is descriptive research. The research aims to explore and describe the ability of Problem-Posing of class VII students of State Junior High School 4 Kintamani notably in the creative dimension. Based on the data obtained, it is found out that generally, Class VII students started to demonstrate their creativity in asking questions/problem related to mathematics. Moreover, by giving mathematical Problem-based Ethnomathematics (MPbE) provides its own coloring in the class discussions, for it is new to the students. They have just realized that the various religious and cultural activities that had been carried out were related to and even rich in mathematical concepts just likewhat they had learned in school. Keywords: Ethnomathematics, Problem Based Learning, Problem Posing